Laser-induced carbonization of Ni-BDC layer on PET: Functional upcycling of polymer wastes towards bend resistive sensor; Materials Today Communications; Vol. 39 - Kogolev D. A. Dmitry Anatoljevich; Kurtsevich E. A. Ekaterina Andreevna; Fatkullin M. I. Maksim Ilgizovich; Zinovyev (Zinovjev, Zinoviev) A. L. Alexey Leonidovich; Gorbunova A. Alina; Rodriguez (Rodriges) Contreras R. D. Raul David; Guselnikova O. A. Olga Andreevna; Boukherroub R. Rabah; Postnikov P. S. Pavel Sergeevich (2024, 2024)
Title screen